THE PORTRAIT OF MORALITIES INSCARLET LETTER NOVEL BY NATHANIEL HAWTORNE - Danul Aristiawan (FKIP, Universitas Banten Jaya, 2023)
The aimed of this research was to analyze and describe about the morality in Nathaniel Hawthorne work entitled The Portrait of morality in Scarlet Letter Novel by Nathaniel Hawthorne. Specially ,this research deal with (1) What are the potrait of moralities by the main characters Hester Prynne ,Arthur Dimmsdale and Roger Chilingworth drawn in Scarlet Letter Novel (2) What are the sequences of these moralities for the main character as the doer of the moralities in Scarlet Letter Novel. This research was descriptive qualitative research. The data were words, phrases, sentences from the first chapter until the last chapter. Theories used used in this research were concerned with novel as a literary work, morals and ethics,morality,morality and religion,morality and law,immorality and the structural approach in literary criticism.This research was catagorized as literary criticms,where the researcher doing analysis, interpretation and evaluation in conducting the research.The writer applies the structural approach in hisresearchbecause to analyzes what moralities characters and what is the consequences of these moralities for the character’s life based on the instrinsic element of this novel.The result of this research were stated as follow: (1)The moralities found in the Scarlet Letter Novel were adultery,hypocrisy and revenge (2)The three main characters get different consequences of thier morality and face the risk of the morality in different ways.Finally the author can conclude that no one is perfect even the priest which supposed tobe the right hand of God.This novel reveal the morality in details and the important point is how this novel is relevant for generation to generation as a guidebook in morality aspect in society.And the writer advise that the next writer will write about literary critism in different point of view.